Legalitas Bahan Bakar berbasis Pirolisis di Indonesia - Arganto, Dave Juan Tirta (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This article examines the legality of pyrolysis-based fuels in Indonesia in the context of renewable energy transition and plastic waste management. Pyrolysis, as a process of thermal decomposition of plastic waste and biomass, offers dual benefits: reducing dependence on fossil fuels and helping to solve the problem of plastic waste. However, its utilisation is constrained by the absence of specific regulations governing the product and its business activities. This study uses normative and conceptual legal methods through an analysis of relevant regulations, particularly the Oil and Gas Law and plastic waste management regulations. The findings show that the absence of a clear legal framework creates uncertainty and hinders the development of the pyrolysis industry. Therefore, it is necessary to establish regulations governing standards, licensing, and the trade of pyrolysis fuel in order to encourage sustainable industrial development and provide legal certainty and protection for the community and the environment.